Perancangan Sistem Informasi Produk Pada Salman Per Berbasis Website Menggunakan Metode Waterfall - Arief Nur Febrianto; Abdullah Al Ghifari; Aditya Rizqiandri Saputra; Saprudin (CV. Shofanah Media Berkah, 2023)
In this modern era, the development of information technology is running so fast. The need for technology is very much needed. One of them is the internet which is used to get information in a short time. On the internet, many consumers are looking for spare parts for certain cars, where consumers can get information and types of products they need. Salman Per is one of the shops / MSMEs that sells various types of car springs. The program that will be taken about website design promotion. Where this program is designed to make it easier to get information about products and buyers for consumers. The author makes written material obtained from interviews with Salman Per, observation books and library references related to promotional media from the internet. Here the author chooses a program with visual studio code application software and uses PHP and HTML languages. Because of its ease of making static websites.